Physical development and physical preparedness of students of special medical group with the disease of vegetative-vascular dystonia of mixed type - A. V. Olchovik (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : theoretically and experimentally substantiate the effect of the author's physical rehabilitation program to the level of physical development and physical fitness of students. Material : the study involved 40 students. Conducted teacher testing: sprinting, flexion and extension arms in emphasis lying on the floor, the rise in the saddle for 1 min., long jump from their seats, jump up from their seats, shuttle run (4 x 9 meters), torso forward from position sitting. Results : author's physical rehabilitation program includes physiotherapy, therapeutic massage, aqua gym, fitball gymnastics, acupressure and health food. The educational process is aimed at: the normalization of blood pressure and heart rate; balance of excitation and inhibition in the central nervous system; reducing the number of relapses; prevention of complications and hardening of the body; increase the level of physical fitness and health; acquire the necessary professional for students of applied skills. At the workshops, special attention is paid to the medical control, self-control and physical exercise techniques, taking into account contraindications. General and professionally applied physical preparation is carried out taking into account the features of students. Conclusions : It is recommended to attract students to self-realization of physical rehabilitation at home.